Screening for fecal occult blood loss in severely malnourished children
Introduction: PEM is the most important and basic hurdle in the triple-M complex of malnutrition, morbidity, and mortality. Very high mortality has been reported in severe PEM. PEM is found to account for about 4 million deaths in children. The study aimed to perform a fecal occult blood test in patients in the age group of six months to five years and also to identify the conditions associated with fecal occult blood loss in pem patients. Materials and Methods: A total of 100 indoor patients of PEM admitted in our pediatric ward were taken as subjects in this study. According to WHO and IAP classification of PEM, severe malnutrition (marasmus, kwashiorkor, and marasmic kwashiorkor) were taken as study group; and mild grades of PEM (grade I and grade II) were taken as a control group. Results: In severe PEM, marasmus (83%) was more common followed by kwashiorkor (14%) and marasmic kwashiorkor (3%); however in mild grades of PEM, grade I PEM was found in 58% and grade II PEM was found in 42%. In severe PEM, pallor (64%), hair changes (38%), and tachypnoea(31%) were major clinical signs; while tachypnoea(36%), dehydration (26%), and pallor (20%